Infecção latente por mycobacterium tuberculosis em portadores de infecção por HIV/AIDS : análise através do uso de teste tuberculínico e teste de liberação de interferon-gama - Herzer, Thaís Lôbo (2012)
People living with HIV have an enhanced chance to develop and to die of tuberculosis (TB). Many studies demonstrate that chemoprophylaxis for latent tuberculosis infection (LTBI) reduces the progression to active TB. Indeed, the diagnosis of LTBI is controversial. In Brazil, the only test approved for use is the tuberculin skin test (TST), however, this test is complicated by several problems due to application and interpretation of the exam. Recently developed interferon-gamma release assays (IGRA) using Mycobacterium tuberculosis-specific antigens have the advantage of decreased cross-reactivity and, therefore, increased specificity. The purpose of this study is to evaluate the adherence of LTBI diagnosis and to compare the results of the QuantiFERON-TB® Gold In-Tube test (QTF-GIT) and TST in a population of HIV-positive individuals from a country with high prevalence of TB. A cross-sectional study was carried out with 351 HIV patients without active tuberculosis, attending outpatient in two reference centers, from November 2007- 2010. At admission, 41.8% had realized TST, 36.3% had been interrogated about TB exposure and 28.4% had performed a chest X-ray. Chemoprophylaxis was offered to 73.3% of TST positive patients. The TST and QTF-GIT results were positive in 25.3% and 6.7% (p<0.001) of the individuals, respectively. The agreement between the two tests was poor (k= -0.037). Drug use (OR 7, 95% CI 1.5-32.1; p=0.01), TB exposure (OR 13, 95% CI 2.7-62.83; p=0.001), previous LTBI prophylaxis (OR 17.5, 95% CI 3.4-90.4; p<0.001), and living outside the state capítal (OR 2.7, 95% CI 1-7.2; p= 0.04) were associated with a positive TST result. There is no association between QTF-GIT positive result and risk factors for TB. TST positive individuals had a higher mean CD4+ cell count than those with TST negative result (535.8 cell/mm3 vs. 373.4 cell/mm3; p=0.006), in contrast to QTF-GIT positive result (277 cell/mm3 vs. 438.3 cell/mm3; p= 0.055). Higher viral load was associated with QTF-GIT positive result (4.8 log10 cop/ml vs. 2.1 log10 cop/ml; p= 0.005). Despite of Brazil being a country with a high burden of TB, more than half the patients have not realized TST, which appears to be more sensitive than QTF-GIT for diagnosis of LTBI. Otherwise, QTF-GIT shows better results in patients with advanced immunosuppression and high viral load. We suggest the use of both tests to increase LTBI diagnosis and decrease the risk of disease progression.